WOMEN’S ROLES IN PUBLIC AND DOMESTIC AFFAIRS IN INDONESIAN FILM 2008-2025 (INTERDISCIPLINARY DISCOURSE STUDY) - Retnosari, Putri; Rengganis, Ririe; Saing, M. Erwan (Prosiding Konferensi Internasional Kesusasteraan, 2025)
This study aims to examine women’s roles in the public and domestic spheres as represented in Indonesian films released between 2008 and 2025. Using an interdisciplinary discourse analysis approach, the study investigates how cinematic narratives construct, reproduce, or challenge gender ideologies in various socio-political contexts. A selection of films from various genres and production years is analyzed to identify patterns of women’s representation, with a focus on character agency, occupational roles, and interpersonal relationships. This method combines elements from critical discourse analysis and visual semiotics to uncover the power structures embedded in cinematic texts. The findings demonstrate a gradual transformation in the depiction of women, with increasing visibility in leadership, activism, and non-traditional professions, although domestic roles remain a dominant theme in many narratives. The study also reveals the persistence of moral and cultural expectations placed on female characters, particularly within the family and community. These results highlight the duality and complexity of women’s representation in Indonesian cinema, reflecting broader social tensions between modernity and tradition.